PEMBANGUNAN EKONOMI ISLAM DENGAN TIPOLOGI ILMIAH - HAFAS FURQANI (Universitas Islam Negeri Imam Bonjol Padang, 2016)
Economic development in Islam, the scientists have different approaches vary. Differences in the approach because of differences in background of science the scientists involved in building the Islamic economy and also differences in terms of vision, ie where Islamic economics as a science would be directed. This paper observes three main approaches taken by scientists in the development of Islamic economics, namely (1) the methodology Usul al-fiqh economic development in Islam, (2) methodological pluralism, which uses a variety of scientific methodology in the scientific tradition of the West and Islam, and (3) the methodology developed in the program of Islamization of knowledge (Islamization of knowledge). The paper tried to examine the basic conception of the methodology used by scientists to build an Islamic economy and also notes the advantages and weaknesses of these approaches.